5G and Wi-Fi 6 Milestones - Gregory, Mark A (Journal of Telecommunications and the Digital Economy, 2020)
Papers in the March 2020 issue of the Journal include discussion on the future of the 51 billion National Broadband Network (NBN), IoT device and system management and the mobile cellular networks in Indonesia. The Telecommunications Association is hosting public forums on the future of the NBN in 2020 at RMIT University in Melbourne. The Australian mobile network operators continue to rollout 5G and Telstra has announced a 5G milestone. In the U.S., the FCC has announced the allocation of 1,200 MHz in the 6 GHz band for unlicensed use including Wi-Fi 6. The Journal welcomes contributions on telecommunications and the digital economy.